2015
DOI: 10.1007/s11032-015-0313-6
|View full text |Cite
|
Sign up to set email alerts
|

The glutathione synthesis may be regulated by cadmium-induced endogenous ethylene in Lycium chinense, and overexpression of an ethylene responsive transcription factor gene enhances tolerance to cadmium stress in tobacco

Abstract: Glutathione (GSH) plays a pivotal role in heavy metal detoxification. Ethylene is one of the important plant hormones, which plays a critical role in triggering plant responses to different stresses such as cadmium (Cd) stress. Ethylene responsive transcription factor (ERF) belongs to one of the largest plant transcription factor families. ERF is known to be induced by ethylene and thus regulate multiple stress responses through the activation of stressrelated genes. Until now, little has been done to explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 60 publications
(68 reference statements)
0
11
0
Order By: Relevance
“…Similarly, Cao et al ( 2014 ) suggested that Cd tolerance in H. vulgare is related to the induction of ethylene signaling. Transgenic N. tabacum plants overexpressing an ERF gene from Lycium chinense displayed greater tolerance to Cd stress than non-transformed plants (Guan et al, 2015 ). On the other hand, ethylene insensitive etr1-1 and ein3-3 A. thaliana mutants were shown to be less sensitive to Li than WT plants (Bueso et al, 2007 ).…”
Section: Ethylene Is a Key Regulator Of Plant Responses To Metal Strementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Cao et al ( 2014 ) suggested that Cd tolerance in H. vulgare is related to the induction of ethylene signaling. Transgenic N. tabacum plants overexpressing an ERF gene from Lycium chinense displayed greater tolerance to Cd stress than non-transformed plants (Guan et al, 2015 ). On the other hand, ethylene insensitive etr1-1 and ein3-3 A. thaliana mutants were shown to be less sensitive to Li than WT plants (Bueso et al, 2007 ).…”
Section: Ethylene Is a Key Regulator Of Plant Responses To Metal Strementioning
confidence: 99%
“…Therefore, increased ethylene biosynthesis upon Cd exposure seems crucial to mount effective defense responses related to GSH (Schellingen et al, 2015a ). In addition, ethylene signaling is implicated in the accumulation of GSH in Al-exposed A. thaliana (Zhang et al, 2014 ), Cd-exposed L. chinense (Guan et al, 2015 ), and A. thaliana plants (Schellingen et al, 2015b ). The increased Cd tolerance of transgenic tobacco plants overexpressing an ERF gene from L. chinense was related to an enhanced expression level of GSH biosynthesis genes (Guan et al, 2015 ).…”
Section: Crosstalk Between Ethylene and Other Players In The Metal Stmentioning
confidence: 99%
“…Exogenously applied GSH positively modulates ethylene biosynthetic pathways enzyme and improves stress tolerance in Arabidopsis Col-0 showing that GSH mediated resistance to stresses occurs via an ethylene signaling pathway (Datta et al, 2015). Recent studies showed that ethylene signaling pathways might be involved in the accumulation of GSH under Cd stress (Guan et al, 2015). Recently, Iqbal et al (2015) have shown that ethylene and N interact to regulate photosynthesis of salt stressed Brassica juncea .…”
Section: Introductionmentioning
confidence: 99%
“…The T 0 kanamycin‐resistant seedlings were further confirmed by RT‐PCR analysis. To evaluate the integration of transgenes and their copy numbers in the genomes of putative transgenic lines of tobacco, Southern blot was performed following previous method . Transgenic T 1 lines that produced only kanamycin resistant T 2 seedlings were considered to be homozygous for the EuWRI1 gene sequence.…”
Section: Methodsmentioning
confidence: 99%